Contracts law and its modern trends: the ecuatorian case - El derecho de los contratos y sus tendencias modernas: el caso ecuatoriano - Méndez Reátegui, Rubén Carlos (2022)
At the international level, in the area of Contract Law, this article begins with a critical review of the current regulatory scenario in Ecuador and its European counterpart. Then, the article aims to comparatively address the objectives, nature and scope of the UNIDROIT Principles, the PECL and the Pavia Draft. They constitute a modern lex mercatoria seeking to go beyond what are the national laws and systems and become the law of business. Above all, the PECL and the DCFR had a crucial indirect effect that influenced jurisprudence and national reforms. Finally, the article identifies the prevailing ius-privatist spirit in Europe as a difference, compared to a model like the Ecuadorian, which is committed to the constitutionalization of the private law (civil and commercial) and a strict delimitation of the principle of private autonomy.